ON THE FORMATION OF ECOAESTHETIC COMPETENCE IN HIGHER EDUCATION - Alijonova Maftuna Makhamadjon kizi (Zeta Repository, 2023)
In the article, the conditions, methods and methods of formation and development of eco-aesthetic competence in the minds of future personnel, which must be implemented in the higher education system, the plan of the work to be done, their effect, the impact on the student's educational activities, each study of environmental knowledge it is mentioned that it is necessary for the younger generation. Today, in the system of higher education, systematic measures to improve students' ecological and eco-aesthetic taste and their results are analyzed.